Loot : how to steal a fortune - Watson, Jude (Scholastic Press, an imprint of Scholastic Inc., 2014)
When Alfie McQuinn, the notorious jewel thief, is killed on a job, his last words to his son, March, are to "find jewels" and this instruction leads the boy to Jules, the twin sister he never knew he had--and the perfect partner to carry on the family business.